2019
DOI: 10.17660/ejhs.2019/84.4.7
|View full text |Cite
|
Sign up to set email alerts
|

Low air humidity during cultivation promotes stomatal closure ability in rose

Abstract: In greenhouse horticulture, evaporative demand varies between seasons. For instance, plants are typically exposed to low relative air humidity (RH) during summer, whereas elevated RH prevails in winter. Since high RH during cultivation impairs stomatal functioning, some opposite changes might be expected, when plants are subjected to long-term low RH. To investigate this, Rosa hybrida 'Pasadena' was cultivated at 40, 60 or 90% RH. Plant performance, transpiration, stomatal closing ability and anatomy were reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 24 publications
(44 reference statements)
1
15
1
Order By: Relevance
“…Devi, Sinclair & Vadez (2010) found that Tr increased over VPD rising, with a break point occurring in some genotypes above which there was little or no further increase in Tr of peanut. Stomatal conductance declined with VPD increasing (Leonardi, Guichard & Bertin, 2000;Talbott, Rahveh & Zeiger, 2003), or RH declining (Fanourakis et al, 2016(Fanourakis et al, , 2019, which implied that Tr did not decline with g s reducing, but increased with VPD rising. And the occurrence of Tr breakpoint might be due to that g s continuously declined and turned to be the restricting factor of Tr.…”
Section: Correlations Between Stomatal Conductance With Transpirationmentioning
confidence: 97%
“…Devi, Sinclair & Vadez (2010) found that Tr increased over VPD rising, with a break point occurring in some genotypes above which there was little or no further increase in Tr of peanut. Stomatal conductance declined with VPD increasing (Leonardi, Guichard & Bertin, 2000;Talbott, Rahveh & Zeiger, 2003), or RH declining (Fanourakis et al, 2016(Fanourakis et al, , 2019, which implied that Tr did not decline with g s reducing, but increased with VPD rising. And the occurrence of Tr breakpoint might be due to that g s continuously declined and turned to be the restricting factor of Tr.…”
Section: Correlations Between Stomatal Conductance With Transpirationmentioning
confidence: 97%
“…Devi et al (2010) found that Tr increased over VPD rising, with a break point occurring in some genotypes above which there was little or no further increase in Tr of peanut. Stomatal conductance declined with VPD increasing (Leonardi, Guichard & Bertin 2000;Talbott, Rahveh & Zeiger 2003), or RH declining (Fanourakis et al 2016;Fanourakis et al 2019), which implied that Tr did not decline with g s reducing, but increased with VPD rising. And the occurrence of Tr breakpoint might be due to that g s continuously declined and turned to be the restricting factor of Tr.…”
Section: Correlations Between Stomatal Conductance With Transpirationmentioning
confidence: 97%
“…Pore area is dynamically adjusted by changes in pore aperture, since pore length is rather rigid during the opening and closure of stomata [10,11]. Active pore aperture adjustments in response to internal (e.g., water status) and external (e.g., environmental) factors are physiologically regulated [12][13][14][15]. Instead, pore length and stomatal density are anatomical features that are set during leaf elongation [10,16].…”
Section: Introductionmentioning
confidence: 99%